2015
DOI: 10.1302/0301-620x.97b1.34236
|View full text |Cite
|
Sign up to set email alerts
|

Is tantalum protective against infection in revision total hip arthroplasty?

Abstract: We hypothesised that the use of tantalum (Ta) acetabular components in revision total hip arthroplasty (THA) was protective against subsequent failure due to infection. We identified 966 patients (421 men, 545 women and 990 hips) who had undergone revision THA between 2000 and 2013. The mean follow up was 40.2 months (3 months to 13.1 years). The mean age of the men and women was 62.3 years (31 to 90) and 65.1 years (25 to 92), respectively. Titanium (Ti) acetabular components were used in 536 hips while Ta co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 31 publications
3
67
2
2
Order By: Relevance
“…Studies have disagreed about whether bearing surface type is associated with a differential risk of PJI. Preliminary work suggests that it may be [2,17], but to our knowledge, ceramic bearing surfaces have not been specifically studied in this way. We therefore asked whether the choice of bearings is associated with differences in the risk of revision for PJI, either within 6 months or over the entire period of observation of 15 years, using a national arthroplasty registry database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have disagreed about whether bearing surface type is associated with a differential risk of PJI. Preliminary work suggests that it may be [2,17], but to our knowledge, ceramic bearing surfaces have not been specifically studied in this way. We therefore asked whether the choice of bearings is associated with differences in the risk of revision for PJI, either within 6 months or over the entire period of observation of 15 years, using a national arthroplasty registry database.…”
Section: Discussionmentioning
confidence: 99%
“…Although the association between several host-related and environmental risk factors is better understood today, the link between the use of different implant materials and PJI has not been clearly defined. Tokarski et al [17] in a retrospective study involving 966 patients found that the use of tantalum acetabular components during revision THA was associated with a lower incidence of subsequent infection when used in patients with periprosthetic joint infection. Bozic et al [2] in a large Medicare database of 148,827 patients undergoing THA found that MoM bearings were associated with higher risk of PJI than MoP and CoC bearings.…”
Section: Discussionmentioning
confidence: 99%
“…Tantalum trabecular metal components are increasingly used in joint reconstruction prostheses and would be another interesting metal to compare in this model. Tantalum has been shown to be associated with reduced infection rate in clinical study, however, this has not been supported by direct antibacterial activity in vitro. …”
Section: Discussionmentioning
confidence: 93%
“…21 These properties ensure sufficient structural support for arthroplasties even in case of major bone loss. 17,19,22,23 Clinical observations even suggest that the use of porous tantalum implants in revision arthroplasties might be associated with a reduced risk of infection, 24 which may be at least partially be explained by in vitro observations showing that it induces less leucocyte dysfunction compared with other materials, and that adherence of staphylococci might be hampered when compared to other common implant metals. 15,25 We describe a case where a Trabecular Metal™ shoulder arthroplasty component was found to have integrated into the surrounding bone, despite long-lasting and ongoing infection.…”
Section: Introductionmentioning
confidence: 99%